“Well Boys, Welcome to the New Law Enforcement”: Reactions to Women on Elite Specialty Units - Todak, Natalie (Women & criminal justice, 2024)
Elite police specialty units are almost exclusively the domains of men. While women have made strides on patrol in many agencies, elite units have not witnessed the same progress. In this study, we interviewed 32 policewomen from across the United States who defied the odds and cultural perceptions of “appropriate” roles for women by earning positions on elite specialty units (i.e., SWAT, K9, motorcycles, and bomb units). Most were the only women on their units and half were the first in their agencies’ histories to enter that space. Participants’ descriptions of department, community, and team members’ responses to their selection are analyzed. Our focus on women who have broken the most formidable gender barriers in law enforcement allows us to better understand the continued exclusion of women and offer recommendations for increasing gender diversity throughout policing.